Clinical safety and efficacy of elliptical thin-flap LASIK using a low-pulse energy femtosecond laser - Hung-Yuan Lin; Ya-Jung Chuang; Steven Wei-Hsin Chang; Pi-Jung Lin (Scientific Reports)
Abstract This study assessed the clinical safety and efficacy of elliptical thin-flap LASIK with a low–pulse energy femtosecond laser in 3 thickness subgroups (85, 90, and 100 μm). A total of 80 patients who underwent bilateral LASIK surgery at Taiwan between April and September 2019 were retrospectively enrolled. Elliptical corneal flaps with wide temporal hinges and inverted-angled side cuts were created. Target flap thickness was calculated on the basis of residual stromal bed thickness and percent tissue altered. Before flap creation, an optical coherence tomography image for visualization of the precut flap position was obtained with the built-in camera. At postoperative month 1, the overall mean logMAR uncorrected distance visual acuity (UDVA) was − 0.04 ± 0.07 (20/18 Snellen), with 96% of eyes achieving UDVA of 20/20 or better. Postoperative mean manifest spherical equivalent was − 0.37 ± 0.42 D at 1 month. The visual and refractive outcomes in each of the 3 subgroups were similar. The achieved flap thicknesses were found to be highly predictable and consistent in the respective thickness subgroups. Optical coherence tomography–guided thin-flap LASIK performed with the low–pulse energy femtosecond laser was found to be safe with no intraoperative or postoperative complications.